2000
DOI: 10.2136/sssaj2000.6462046x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Soil–Landscape and Ecosystem Properties Using Terrain Attributes

Abstract: The study on the relationship between the soil aggregates stability assessed using water stable aggregate (WSA) index and the selected terrain and soil properties was performed on a morphologically diverse study site in Chernozem soil region of Southern Moravia. Soil analyses and detailed digital elevation model processing were the main methods adopted in the study. The soil structure stability is negatively influenced by the soil material removal from the steep parts of the back-slope and re-deposition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
240
2
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(275 citation statements)
references
References 13 publications
17
240
2
7
Order By: Relevance
“…It is noticeable that the lower slope is the segment with highest intensity of water flow (Figure 1) and that in this segment the contour for most of the properties studied are perpendicular to the slope of the hill (Figure 2), revealing the variability of these properties. This isoline pattern on the map corroborate the results reported by GESSLER et al (2000) that the characteristic of the water flow determines different areas of erosion and deposition. It is observed that higher values of Ca, Mg, K, V% and clay content are recorded on the lower slope (flat shape) due to the direct action of water surface flow by depositing material on this slope.…”
Section: Resultssupporting
confidence: 90%
“…It is noticeable that the lower slope is the segment with highest intensity of water flow (Figure 1) and that in this segment the contour for most of the properties studied are perpendicular to the slope of the hill (Figure 2), revealing the variability of these properties. This isoline pattern on the map corroborate the results reported by GESSLER et al (2000) that the characteristic of the water flow determines different areas of erosion and deposition. It is observed that higher values of Ca, Mg, K, V% and clay content are recorded on the lower slope (flat shape) due to the direct action of water surface flow by depositing material on this slope.…”
Section: Resultssupporting
confidence: 90%
“…Lower values of soil organic matter were found under pasture areas, which is the predominant land use in this watershed. Water distribution in landscapes stricly controls soil carbon dynamics (Gessler et al, 2000), even though the floodplain did not show higher values of soil organic matter, which may be due to the very high vertical and lateral spatial variability of characteristics, typical of these lowland environments. Soil organic matter maps showed higher values in the convex summit.…”
Section: Prediction Mapsmentioning
confidence: 87%
“…Soil organic matter maps showed higher values in the convex summit. Gessler et al (2000) highlight the combination of higher weathering-leaching, very low natural fertility, low temperatures in the past, and limited activity of microorganisms might have contributed for the organic matter accumulation in this landscape position.…”
Section: Prediction Mapsmentioning
confidence: 92%
See 1 more Smart Citation
“…Changes in soil depth is connected with processes of soil formation including chemical weathering of parent rock, loss of material formed through this weathering and transportation of soil by means of erosion (Fu et al, 2011). Besides the age pf soil formation, soil depth is also directly associated with topography, parent material, living organisms and climate (Gessler et al, 2000). The great degree of steepness in the study area caused soil depth to be low.…”
Section: Figure 1 Study Area Mapmentioning
confidence: 98%